Insentif Budidaya Pala di Kecamatan Somagede, Kabupaten Banyumas - Nunik Kadarwati; Istiqomah Istiqomah (EKO-REGIONAL, 2011)
This paper aims to measure the economic efficiency, poverty and well-being of nutmeg farmers in Somagede district, Banyumas regency. The respondents consist of 30 farmers selected by snowball sampling due to difficulty in getting sampling frame. Economic efficiency is the ratio between revenue and expenses. Economic efficiency of more than unity means that a particular business is profitable. Poverty is measured by comparing farmers’ percapita income with poverty line, while well-being is compared to regency’s living standard. The results show that in the long-run, nutmeg farming is highly profitable; however in the short-run, it is not attractive due to lead time (5-7 years from planting to harvest). Among 30 respondents, only one farmer is categorized as poor, while the rest are not poor. However, from the well-being perspective, only five respondents are of good well-being. Interventions to improve skills in farming and adding value to nutmeg products are therefore recommended. Keywords: nutmeg farming, economic efficiency, poverty, well-being